Emissions of Local Heavy Fuel Oils - A. Rabah, Ali; Abusief Abbas, Mustafa (University of Khartoum Engineering Journal, 2022)
This work aims to measure the emission level of local heavy fuel oils used in boilers and furnaces. Two types of fuel oil are commonly used in the Sudan. These are heavy fuel oil (HFO) produced in Elobied refinery and heavy coker gas oil (HCGO) of Khartoum refinery. The experimental combustion set up consists of a combustion chamber, a burner, a stack and a forced draught fan. Besides measurement of temperature and concentrations of flue gas emissions (CO2, H2O, CO, SOx, NOx), combustion air and fuel flow rates were measured. A theoretical combustion model was developed to predict the combustion performance. The model employs material balance, energy balance and reaction kinetics. It was used to validate the experimental results. The elemental analysis of fuel oils revealed that they have low sulfur content. It was also found that HCGO has high concentrations of heavy metals (Fe, V, Ni, Ca, Zn). The rheological test revealed that HFO has a non-Newtonian behavior and high atomizing temperature. The combustion performance parameters of air fuel ratio, excess air, emissions were evaluated. The results revealed significant emissions of CO and NOx in particular at low fuel air ratio (<1.1). The lowest emission level is found to be at 15 to 20 % excess air.